If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7w + -9 = 6w + -2 Reorder the terms: -9 + 7w = 6w + -2 Reorder the terms: -9 + 7w = -2 + 6w Solving -9 + 7w = -2 + 6w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-6w' to each side of the equation. -9 + 7w + -6w = -2 + 6w + -6w Combine like terms: 7w + -6w = 1w -9 + 1w = -2 + 6w + -6w Combine like terms: 6w + -6w = 0 -9 + 1w = -2 + 0 -9 + 1w = -2 Add '9' to each side of the equation. -9 + 9 + 1w = -2 + 9 Combine like terms: -9 + 9 = 0 0 + 1w = -2 + 9 1w = -2 + 9 Combine like terms: -2 + 9 = 7 1w = 7 Divide each side by '1'. w = 7 Simplifying w = 7
| x^2=6-x | | f(11)=11-7 | | 2x+8y=10 | | f(11)=2-7 | | 15x+32=15x-47 | | 4x+2+3+88=180 | | 4x+2+3+3+88=180 | | (4x^2-9)(x^2-2x+1)=0 | | 5p-4=3p+8 | | 5w-6=4w-3 | | 2(x+2)=4x-14 | | 5x+1=3x-21 | | 2x^4-5=27 | | 20h-(5h+9)+(7-9h)=(12h-5) | | 2=3x+x*x | | x^2+27x+124=0 | | 3+7(x-3)=6(x-3)(x-3) | | x^8+x^4+1=0 | | x^4+3x^2-5=0 | | 7x-12=3x+10 | | x-2y+3x+y= | | 3x-2x+4x= | | 4m+2=2m+9 | | 2x+5=x+8 | | 5y=3y+12 | | 5x+4=7x-4 | | 14x+8y=102 | | 102=x*14+y*8 | | k^2x-k^2+x=2kx-3k+2 | | 3(f+7)=24 | | 7x-8x+12-7tx=49 | | 25(68)-7w=800 |